Effect of GLP-1 Receptor Agonists in the Cardiometabolic Complications in a Rat Model of Postmenopausal PCOS - Torres Fernandez, Edgar D (Endocrinology, 2019)
Polycystic ovary syndrome (PCOS) is characterized by hyperandrogenism and ovulatory dysfunction. Women with PCOS have an elevated prevalence of cardiometabolic risk factors that worsen after menopause. Liraglutide (Lira), a glucagon-like peptide-1 receptor agonist, has shown beneficial metabolic effects in small clinic trials in reproductive-age women with PCOS. We have shown that chronic hyperandrogenemia in an experimental model of postmenopausal PCOS is associated with an adverse cardiometabolic profile and upregulation of the intrarenal renin-angiotensin system (RAS). We analyzed the effect of Lira in the cardiometabolic profile, intrarenal RAS, and blood pressure (BP) in postmenopausal PCOS. Four-week-old female Sprague Dawley rats were treated with DHT or placebo for 17 months. Lira administration during the last 3 weeks caused a bigger reduction in food intake, body weight, fat mass, and homeostasis model assessment of insulin resistance index in PCOS than in control rats. Moreover, Lira improved dyslipidemia and elevated leptin levels in PCOS. In contrast, Lira decreased intrarenal expression of RAS components only in the control group. Lira transiently increased heart rate and decreased BP in control rats. However, Lira did not modify BP but increased heart rate in PCOS. The angiotensin-converting-enzyme inhibitor enalapril abolished the BP differences between PCOS and control rats. However, Lira coadministration with enalapril further reduced BP only in control rats. In summary, Lira has beneficial effects for several cardiometabolic risk factors in postmenopausal PCOS. However, hyperandrogenemia blunted the BP-lowering effect of Lira in postmenopausal PCOS. Androgen-induced activation of intrarenal RAS may play a major role mediating increases in BP in postmenopausal PCOS.